Acculturation of Javanese and Chinese Culture in Rural Tourism in Desa Wisata Besani - Kevin Gustian Yulius (Advances in Tourism Studies, 2023)
The research paper investigates the cultural exchange between Javanese and Chinese traditions in rural tourism at Desa Wisata Besani, Central Java. Rural tourism has become popular among international travelers seeking authentic experiences and sustainable community engagement. Desa Wisata Besani, known as the "Acculturation Gate of Java-China," offers a unique blend of Javanese and Chinese influences, making it an intriguing destination. The study uses qualitative methods to understand the factors attracting tourists and the impact on the local community's livelihood and identity. The village's strengths, such as its rich cultural heritage and strategic location, contribute to its aspiration of becoming a thriving rural tourism destination and a cultural exchange hub. The rising interest in cultural tourism and China's investments present growth opportunities for the village. Integrating Mandarin language learning into the tourism experience further enhances its appeal to Chinese tourists. The study acknowledges limitations and suggests future research directions. In conclusion, Desa Wisata Besani showcases the potential of rural tourism in fostering cultural understanding and appreciation, benefiting both tourists and the local community.